Counter-Movements in the Sciences
XVI, 294 p.
Keywords: Heretical thoughts in an orthodox series on sociology of the sciences? Devils and science between the covers of one book? Games with ambivalence to mask collective uncertainty? We anticipate similar future reactions from readers or reviewers when assessing the way in which this volume has been assembled. But writings on counter-science, like the history of colonialism, are usually written by the winners, therefore unequivocally partial and only too often lacking in social imagination. In seeking to redress the balance, we admit to having been fully receptive to the latter, of having displayed an un measured degree of sympathy with heretics and outsiders, including practising scientists, and to letting science defend itself. The antithetical relationship implied in the volume's title - Counter-movements in the Sciences - stands for what we regard as an ongoing, open-ended process. In collecting material for this volume, we have brought together voices speaking from different quarters: there are those who, although modestly claiming to speak only for them selves, have set out to question sacred assumptions of scientific faith or to cast doubt on well-known claims scientific knowledge holds over other forms of knowledge; others have undertaken to demonstrate the fragility, ifnot untenability of attempts at demarcation between science and other systems of belief or practice or shown that demarcations between different forms of rationality rest on other than methodological grounds; finally, those who wish to re-arrange, by mapping out some meta-point of surveillance, familiar territory, showing the need for rearrangement and.